Place Naming of Tourist Destinations in Banyumas Central Java - Oktaviana, Ika; Junawaroh, Siti (Proceedings of International Conference on Islamic Civilization and Humanities, 2023)
Banyumas has a variety of fascinating tourist destinations to visit. Tourism diversity includes natural, cultural, and educational tourism. Moreover, each tourism destination in Banyumas has a unique and diverse name. This study attempts to describe how the tourism destination names in Banyumas are formed. This study explains the meaning of the place naming process of tourist destinations in Banyumas, Central Java. This study explores a corpus of 30 tourism destination names in Banyumas. It is analyzed by identifying the place naming process semantically. In this investigation, the results of this study expose explicitly that the names are interestingly formed by some aspects, namely geographical/nature appearance, similarity, historical background, location, place function, and place description. It is also found that geographical/nature appearance aspects are the dominant type for naming tourist destinations. Hence, the naming place of tourist destinations is uniquely embodied to inform the types, characteristics, or locations of the tourist destinations to attract tourists and create its branding.